2001
DOI: 10.1007/bf03028172
|View full text |Cite
|
Sign up to set email alerts
|

Lung isolation in thoracic anesthesia, state of the art

Abstract: Although the incidence of cases with the original indications for lung isolation such as abscess and hemoptysis has decreased, lung isolation is required with increasing frequency in an ever-widening spectrum of clinical situations. The preference of anesthesiologists has oscillated between bronchial blockers and single or double-lumen tubes for the past 50 yr. At present, double-lumen tubes continue to have the widest application for providing safe reliable lung separation in the majority of cases. However th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
2
13
0
2
Order By: Relevance
“…Clinical factors and traditional risk factors remain inadequate to predict the variability in AKI after cardiac surgery. Ethnicity has been shown to be a predictor of AKI in the Western population with African Americans having a higher risk compared to their Caucasian counterparts (1). Our study also demonstrated a race effect with Indians and Malays having a higher risk of developing AKI after cardiac surgery compared to Chinese (2).…”
Section: Monash University Victoriasupporting
confidence: 56%
See 1 more Smart Citation
“…Clinical factors and traditional risk factors remain inadequate to predict the variability in AKI after cardiac surgery. Ethnicity has been shown to be a predictor of AKI in the Western population with African Americans having a higher risk compared to their Caucasian counterparts (1). Our study also demonstrated a race effect with Indians and Malays having a higher risk of developing AKI after cardiac surgery compared to Chinese (2).…”
Section: Monash University Victoriasupporting
confidence: 56%
“…For 2012 the Health Roundtable data (collected from 143 health institutions) demonstrated that SCGH had the shortest median and average hospital stay for major chest procedures and procedures for malignant neoplasm of the bronchus (1). Median length of stay was 3.3 and 3.1 days respectively.…”
mentioning
confidence: 99%
“…Actuellement la plupart des interventions en chirurgie thoracique exigent une isolation pulmonaire ou une intubation uni pulmonaire, réalisée par les TDL ou des bloqueurs bronchiques. 10,11 Les TDL peuvent poser des problèmes d'intubation, même en l'absence de données prédictives d'intubation difficile. Ces problèmes sont d'ordre technique en rapport avec le type de tube et sa morphologie spéciale (diamètre, taille, courbure de l'extrémité bronchique, présence de l'éperon et rigidité de l'ensemble du tube).…”
Section: Discussionunclassified
“…O ne ‐ lung ventilation (OLV) in the lateral decubitus position is an established procedure during thoracic surgery. However, OLV significantly affects lung mechanics and ventilation to perfusion (V/Q) matching, causing important gas exchange alterations leading to hypoxemia in 7–10% of cases (1–4).…”
mentioning
confidence: 99%